Chronic myeloid leukemia patients’ adherence to peroral tyrosine kinase inhibitors compared with adherence as estimated by their physicians - Kekäle, Meri (Patient Prefer Adherence, 2014)
PURPOSE: To evaluate chronic myeloid leukemia (CML) patients’ adherence to peroral tyrosine kinase inhibitors in Finland and to compare this with adherence as estimated by their physicians. Other aspects studied included how patients’ knowledge of the disease and its treatment influence adherence. MATERIALS AND METHODS: A total of 120 CML patients were contacted between June 2012 and September 2013 in eight secondary or tertiary care hospitals in Finland. Of these, 86 participated in the study. This covers approximately 20% of all Finnish CML patients. The mean age was 57.8 years and 52% were male. Of the patients, 79.1% were using imatinib, 10.5% dasatinib, and 10.5% nilotinib. The patient-reported adherence (experienced adherence) was evaluated using the eight-item Morisky Medication Adherence Scale (MMAS). In addition, the treating physicians were asked to give their subjective opinion on their patients’ adherence (observed adherence). The experienced adherence was compared with the observed adherence using a three-level rating system (high, medium, low). All patients were personally interviewed and their demographic data collected. The statistical analysis of the data was based on descriptive statistics presented as frequencies, percentages, means, and medians. The kappa coefficient was calculated between the patient’s and the doctor’s assessment of adherence. RESULTS: A total of 23% (20/86) of the patients were fully adherent according to the MMAS, while physicians evaluated 94% (80/86) of the patients as fully adherent. The physicians’ estimate was too optimistic in 73% of cases. The discrepancy was confirmed by a kappa value of −0.004. The patients’ knowledge of the disease and its treatment was poor in all adherence levels. CONCLUSION: The patient-reported adherence to tyrosine kinase inhibitor treatments in Finland was found to be the same as that found in the majority of previous studies. However, there seems to be a very weak agreement between the patient’s and the physician’s assessment of adherence. This study suggests that physicians overestimate the adherence of CML patients and base their assessment primarily on the clinical treatment response.